[2+2] Cycloadduct of Titanium Silylidene and Benzonitrile. Issue 39 (29th August 2019) - Lee, Vladimir Ya.; Horiguchi, Satoru; Gapurenko, Olga A.; Minyaev, Ruslan M.; Minkin, Vladimir I.; Gornitzka, Heinz; Sekiguchi, Akira
Abstract : The first [2+2] cycloadduct of the transition metal silylene complex and nitrile was synthesized by the reaction of titanium silylidene and benzonitrile. Only one regioisomer was exclusively isolated, in which the C atom of the nitrile group was bound to titanium whereas the N atom was bound to silicon, which was explained by steric effects. Based on its NMR spectroscopic and X‐ray crystallographic data, this [2+2] cycloadduct was classified as possessing predominantly metallacycle resonance structure. Abstract : The first [2+2] cycloadduct of a transition metal silylene complex and nitrile was synthesized by the reaction of titanium silylidene and benzonitrile. Based on its NMR spectroscopic and X‐ray crystallographic data, this compound has predominantly metallacycle resonance structure.